IMPLEMENTASI VISUAL MERCHANDISING PADA TOKO RITEL DI INDONESIA - KARSIWAN, CITRA PURNAMASARI WIDJAJA (Universitas Katolik Widya Mandala Surabaya, 2013)
Along with the increasing needs of the community to make growth retail business (retailing) should be more active in the face of growing competition. Visual merchandising is something that is very important in determining the success of a retail business. Visual merchandising when implemented correctly will help retailers to increase sales and increase profits. Visual merchandising is everything customers observe, both exterior and interior, which creates a positive image of the business and result in attention, interest, and the reaction on the part of the customer. Visual merchandising includes graphic design, signage, billboards, layout space management, visual planning, structuring and planning mannequin good inventory management. This paper aims to discuss the implementation of visual merchandising at the retail store in Indonesia by using the example of the discussion of the Matahari Department Store and Hypermart. The results of this paper are in terms of visual merchandising concepts and techniques can be a solution for retailers in their efforts to gain and retain customers. Visual merchandising can adapt to changes in the retail environment.